The Dynamics of Secondary Mangrove Forests in Bintuni Bay, West Papua after Harvested on the First 30-Year Rotation Cycle - Ruhuddien Pandu Yudha; Solehudin; Wahyudi; Mériadec Sillanpää (Jurnal Sylva Lestari, 2022)
Mangrove forests in Bintuni Bay, West Papua, Indonesia, have been managed for timber extraction since 1988 to produce wood chips using a 30-year rotation cycle. The first rotation cycle was completed, resulting in secondary mangrove forests with various stand ages (1−30 years). A large-scale forest inventory was conducted for all harvested blocks to recognize actual standing stock for the 2021−2030 management plan. A total of 434 quadrat plots (20 m x 20 m) covering 17.36 ha each were used to observe forest standing stock. The results present the dynamics of secondary mangrove forests after the initial rotation cycle. At the end of the first cycle (30-year-old stand), secondary mangrove forests provided a volume of 290.12 m3 ha-1 and potential extractable biomass of 203.03 ton ha-1 with mean diameter, basal area, and stem density of 16.91 cm, 29.18 m2 ha-1, and 1,370 stem ha-1, respectively. Annual increment of volume, biomass, and diameter were estimated to be 9.67 m3 ha-1 year-1, 6.77 ton ha-1 year-1, and 0.56 cm year-1, consecutively. The dynamics of secondary mangrove forests could provide significant information in the context of the management plan and implementation of the silviculture system to ensure the sustainability of utilization in managed mangrove forests. Keywords: Forest regeneration, Silviculture, Standing stock, Sustainable management, Timber utilization